FAKTOR YANG MEMPENGARUHI MINAT PEMBELIAN PRODUK RAMAH LINGKUNGAN (STUDI KASUS PADA GEN Z DI JABODETABEK) - Eka Agustha Prasetya Utama; Edi Komara (Ibs Press, 2023)
Environmental problems have generated a trend to preserve the environment and have brought changes in consumer attitudes and behavior by buying environmentally friendly products. This study seeks to test interest in purchasing environmentally friendly products. This research was conducted in 2020, with the variables of environmental consciousness, environmental knowledge, environmental attitude, and purchase intention towards green products. This research uses a descriptive research design approach with empirical data collected through an online survey the sample in this study is the Z generation in Jabodetabek. The empirical data is then processed using the Structural Equation Modeling approach to test a number of proposed hypotheses. The results of this study are as follows: 1) Environmental Consciousness has a significant positive effect on Purchase Intention towards Green Products, 2) Environmental Consciousness does not have a significant effect on Environmental Attitude, 3) Environmental Knowledge is proven to have a significant positive effect on Environmental Attitude, 4) ) Environmental Knowledge has no significant effect on Purchase Intention towards Green Product, 5) Environmental Attitude is proven to have a significant positive effect on Purchase Intention towards Green Product.